Antibacterial and antibiofilm efficacy of the preferred fractions and compounds from Euphorbia humifusa (herba euphorbiae humifusae) against Staphylococcus aureus. (24th April 2023) - Wu, Xiying; Ma, Guang-Lei; Chen, Hao-Wei; Zhao, Ze-Yu; Zhu, Zi-Ping; Xiong, Juan; Yang, Guo-Xun; Hu, Jin-Feng
Abstract: Ethnopharmacological relevance: Euphorbia humifusa Willd., known as Di-Jin-Cao in Chinese, has long been utilized as a traditional herb for the treatment of furuncles and carbuncles mainly caused by Staphylococcus aureus infection. Despite extensive chemical and pharmacological studies reported previously for E. humifusa, the antibacterial and antibiofilm activities against S. aureus as well as the related mechanism of action (MoA) remain largely obscure. Aim of the study: To investigate the antibacterial and antibiofilm activities of the preferred fractions and compounds from E. humifusa against S. aureus and assess the associated MoA. Materials and methods: The bioactive fractions and compounds were obtained from the 75% ethanol extract of E. humifusa (75%-EEEH) with the assistance of the related antibacterial and antibiofilm screening. Their antibacterial activities were determined using the broth microdilution method, whilst the inhibition of biofilm formation and the disruption of preformed biofilm were assessed by crystal violet staining and confocal laser scanning microscopy (CLSM). To achieve more effective therapies, the combinatory effects of different components were also studied. The biofilm metabolic activities of isolated compounds were evaluated by 2, 3-bis-(2-methoxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carboxanilide (XTT) reduction assay. The scanning electron microscopy (SEM) and quantitative real-time polymerase chain reaction (qRT-PCR) were employed to explore the antibiofilm mechanism. Results: Fractions DJC06 and DJC07 collected from the ethyl acetate extract of the 75%-EEEH exhibited antibacterial activity (MIC = 256 μg/mL) against S. aureus and further separation of these two fractions led to the isolation and characterization of 22 compounds. Among the isolates, luteolin (LU), quercetin (QU), and kaempferol (KA) are the verified components associated with the antibacterial and antibiofilm activities by displaying individual or combinational MIC values of 8–128 μg/mL and 70.9–99.7% inhibition for biofilm formation. Importantly, QU and KA can work in synergy with LU to significantly enhance the efficacy via destroying cell integrity, increasing membrane permeability, and down-regulating the biofilm-related gene expression. Conclusions: The preferred fractions and compounds from E. humifusa exerted desired antibacterial and antibiofilm efficacy against S. aureus via a MoA involving cell morphology disruption and altered genes expression. The findings herein not only support its traditional use in the treatment of furuncles and carbuncles, but reveal E. humifusa is a potential source for producing promising antibiofilm alternatives against S. aureus and highlight the isolated components (LU, QU, KA) that can potentiate the efficacy when used in synergy. Graphical abstract: Image 1 Highlights: Fractions and compounds from Euphorbia humifusa exerted desired antibiofilm activity. Luteolin (LU), quercetin (QU) and kaempferol (KA) represent the bioactive components. QU and KA can work in synergy with LU to enhance the bioactivities against S. aureus. QU + LU could down-regulate fnbA expression at the biofilm adhesion/attachment stage.